2018
DOI: 10.4172/2155-9600.1000682
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Moisturizing Effect of Collagen Peptides Taking Orally

Abstract: The skin is said to be "a mirror reflecting who you are inside". Indeed, beauty is not simply one's external appearance, but it also comes from within; beauty also comes from paying attention to both physical and mental health. Attention to have attractive skin has been on the rise in many age groups over the last decade; even women in their 20's often expresses the desire to look younger and fresher. Products containing collagen peptides drive the growth of the health and beauty and food and beverage industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Ceramide content was decreased in mouse model of skin photoaging, in which skin barrier damage was induced and remained similar to the normal group when fish collagen was administered [35]. Treatment of three-dimensional cultured human skin models with collagen peptides increased the transcript-level expression of ceramide synthases, such as serine palmitoyltransferase-2 and β-glucocerebrosidase [36]. These results suggest that collagen retained the total ceramide content by maintaining lipid profile in the skin [35].…”
Section: Introductionmentioning
confidence: 73%
“…Ceramide content was decreased in mouse model of skin photoaging, in which skin barrier damage was induced and remained similar to the normal group when fish collagen was administered [35]. Treatment of three-dimensional cultured human skin models with collagen peptides increased the transcript-level expression of ceramide synthases, such as serine palmitoyltransferase-2 and β-glucocerebrosidase [36]. These results suggest that collagen retained the total ceramide content by maintaining lipid profile in the skin [35].…”
Section: Introductionmentioning
confidence: 73%
“…The oral intake of collagen peptides has been found to increase the moisturizing capacity of the skin by enhancing the moisture content of the stratum corneum. Collagen is well absorbed into the body in the form of amino acids (AA), dipeptides, and tripeptides after ingestion via the oral route ( 95 ). Some research works have displayed the remarkable absorption of two main CPs, i.e., prolyl-hydroxyproline (Pro–Hyp) and hydroxyprolyl-glycine (Hyp–Gly) that exert chemotaxis on dermal fibroblasts and reinforce cellular proliferative ability ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rice-derived peptides (molecular weight < 300 Da) obtained after special processing of rice-bran protein, greatly inhibit activity of MMPs and stimulate the expression of hyaluronan synthase 2 genes in human keratinocytes cells [24]. Manosroi et al (2012) successfully produced formulas containing niosomes encapsulated in rice-bran peptides, and demonstrated that they have ideal clinical anti-aging properties [25].…”
Section: Enzyme-inhibitory Peptidesmentioning
confidence: 99%